Use of sun gear orbits to obtain the load sharing in planetary transmissions and its impact in the tooth load. (March 2023) - Sanchez-Espiga, J.; Fernandez-del-Rincon, A.; Iglesias, M.; Viadero, F.
Highlights: Load per tooth in planetary transmission compared with the load per planet. New representation of orbits to assess the load sharing in ESSP transmissions. Impact of the floatability and number of planets in the load per tooth. Impact of the floatability and number of planets in the sun gear orbits. Comparison of scenarios with in phase or sequential mesh phasing. Abstract: The present work assesses the possibility of using the orbits described by the sun gear in order to analyse the load sharing ratio in planetary gear transmissions. Furthermore, the current work is extended to observe the impact of the floatability and different tangential pinhole position errors in the load borne in a single contact between a pair of teeth in comparison to the load per planet. Therefore, it highlights the inaccuracy of the load sharing ratio (LSR) as an indicator of the overload in one tooth of the planet. Moreover, the use of the orbits represented with respect to a rotating reference provides helpful information to determine the overloads and underloads in the planets due to the existence of a tangential error in sequentially phased transmissions. Therefore, this proposal provides a simpler solution to the measurement of the LSR in planetary transmissions with different numbers of planets than the use of strain gauges.